Educación financiera y toma de decisiones de inversión en estudiantes de la Facultad de Ciencias Económicas y de Negocios - Universidad de la Amazonía Peruana; Iquitos 2024 - Arteaga Mahoma, Jordano Stephano (2025)
The objective of the research was to identify the relationship between financial education and investment decision-making in students of the Faculty of Economics and Business Sciences of the National University of the Peruvian Amazon, Iquitos, 2024, with type of research quantitative scope, non experimental design and type of cross-sectional or transactional design with correlational study scope, included a population of 2409 and a sample of 331 students from the accounting, administration, economics and business degree at the Faculty of Economic and Business Sciences of the Universidad Nacional Amazonia Peruana, the survey was used as a data collection instrument, it was concluded that there is a strong positive correlation with a Spearman's Rho value of 0.746 between financial education and financial decision-making. investment, indicating that a higher level of financial education is associated with more informed financial decisions, in addition to All the correlations found are highly significant (p < 0.01), which indicates that the observed relationships are real.